Taking the Social Justice Fight to the Cloud: Social Media and Body Positivity. (4th May 2021) - Zavattaro, Staci M.
Abstract : Fat. The word has a negative, vitriolic meaning, but there are body positivity activists trying to reclaim the word as a descriptor rather than derogatory term. People in larger bodies are often ostracized, not allowed to fully participate in society, making this a social justice issue. Social media are becoming primary tools people use to shape and change discourse that frames fat bodies as lesser members of society or a problem to be controlled (think the "obesity epidemic"). This conceptual article details how social media platforms can be used to change the dominant narrative, pushing the scholarship beyond realizing that social media are being used for this change-related purpose. Using Sementelli's map of the individual, I highlight some Instagram accounts promoting either the dominant weight loss narrative or a body positive one, showing how people can use their power (or reclaim it) to shape discourse related to social justice and body positivity.